Punctual Relations: Thomas Browne's Rhetorical Reclamations. - Preston, Claire (Studies in Philology)
This essay situates Thomas Browne's late Musaeum Clausum, a fictive encycopedic catalogue or spoof catalogue, within the early modern culture of collecting. I argue that repeated rhetorical figures and effects in this text enforce a theme of absence, irrecoverability, and anonymity, and I suggest that Browne's attitude here toward losses in learning is enervated and pessimistic in relation to the more typically optative mood of discovery and intellectual recuperation that characterizes much of his earlier writing. Browne relies on two rhetorical figures in particular--meronymy and ekphrasis--to structure his disquisition on loss within the framework of collecting. Browne's late fascination with the fragmentary and dispersed indicates the belatedness and probable futility that he finds in the redemptive projects fashioned by Baconian investigators seeking to reassemble the knowledge that remains scattered throughout the world.